Sheet-like MoO₃ nanostructures with improved charge storage: Relationships among structural, optical, and electrochemical properties - A.P. Nagendra Babu; N. Pradeep; C.G. Renuka (Next Energy, 2025)
The molybdenum trioxide (MoO₃) nanosheets were synthesized via thermal decomposition and thoroughly characterized for their structural, morphological, optical, and electrochemical properties. X-ray diffraction (XRD) confirmed orthorhombic phase purity with crystallite sizes of 69–97 nm. Raman and FTIR spectroscopy revealed key Mo–O and MoO vibrational modes, while X-ray photoelectron spectroscopy (XPS) confirmed oxidation states. Field emission scanning electron microscope (FESEM) and transmission electron microscopy (TEM) showed sheet-like morphology, and energy-dispersive X-ray spectroscopy (EDX) validated elemental composition. UV–vis spectroscopy indicated direct and indirect band gaps of 2.800–2.977 eV and 2.566–2.940 eV, respectively. Electrochemical performance, assessed via cyclic voltammetry (CV), galvanostatic charging-discharging (GCD), and electrochemical impedance spectrometry (EIS), demonstrated excellent capacitance (217.30 F/g), energy density (21.47 Wh/kg), and power density (2118.65 W/kg). When integrated into coin cells, MoO₃ nanosheets exhibited a specific capacitance of 48.39 F/g, with an energy density of 31.93 Wh/kg and power density of 2903.26 W/kg. These findings underscore their strong potential in advanced energy storage applications.